Nilai Karakter dalam Ritual Chiong Shi Ku pada Etnis Tionghoa di Kota Singkawang Kalimantan Barat - Chalista; Darmawan, Diaz Restu; Efriani (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2021)
Chiong Shi Ku or Sembahyang Rampas is one of the ritual events of Confucian teachings in the Chinese community. Rituals that are often held on the peak day of the closing of the grave prayers fall on the 15th Chinese New Year of the 7th month of the Chinese calendar. The Chiong Shi Ku ritual is included in a series of Burial Prayers which are routinely carried out by the Chinese community for 2 times a year, namely the Ceng Beng event and the Hungry Ghost Festival. Common activities carried out during the Grave Prayer are cleaning the graves of family ancestors, providing offerings and burning food and money for the afterlife made of paper. This article is based on research that aims to describe the values ​​of cultural education and character contained in the Chiong Shi Ku ritual which is still practiced by the Chinese community in Singkawang. The methods used in the preparation of this article are field observations and qualitative methods by directly interviewing informants who are active in the Chiong Shi Ku ritual in the city of Singkawang. Based on the findings and data analysis, this article concludes that Chiong Shi Ku is a cultural ritual for the Chinese community that has cultural educational values ​​and important characters for the Chinese community. These values ​​include religion, tolerance, discipline, curiosity, responsibility, piety, friendship and social care.